Analisis Manajemen Risiko Pada Bank Syariah: Tinjauan Literatur - Roos Nelly; Saparuddin Siregar; Sugianto Sugianto (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Due to their unique risk profile, Islamic banks face challenges in risk management. This study aims to review the risks faced by Islamic banks. This study explores risk practices through selected literature and describes the risks faced by Islamic banks. The results show that there are several risks faced by Islamic banks including: credit risk, liquidity risk, operational risk, legal risk, withdrawal risk, benchmark risk and fiduciary risk. Another finding is that Islamic banking is riskier than conventional banks due to its uniqueness in providing financing. In addition, this is also due to an immature money market, limited availability of lender of last resort facilities from the central bank, and a lack of market infrastructure. Islamic banks from the literature analyzed, have not shown to have developed effective solutions to manage the risks of conventional banks and face their own unique risks. Keywords: Islamic Banking, Management, Risk